PERANCANGAN TPS SEBAGAI SARANA PENGELOLAAN SAMPAH DI SMAN 1 KAPUAS BARAT ( Design Of Tps As A Means Of Waste Management At Sman 1 Kapuas Barat ) - Tahan Tarip; Dony Setiawan Siswoyo Putra (Fakultas Teknik Universitas Kristen Palangka Raya, 2022)
Garbage has always been a serious problem, this problem arises because there is still a lack of awareness to participate and socialize in waste management. Waste management facilities are of course very much needed so that the waste management program can be carried out properly, especially at SMAN 1 Kapuas Barat. This study uses a quantitative method by discussing the generation and composition of waste at SMAN 1 Kapuas Barat as the basis for the proposed design of a Waste Treatment Site (TPS) in this area. The reference used is SNI 19-3964-1994 concerning Methods for Taking and Measuring Sample Generation and Composition of Municipal Solid Waste. The results of the study stated that the current amount of waste generation reached 0.453 kg/day. The composition of waste at SMAN 1 Kapuas Barat consists of 56.6% organic waste from food and yard waste, 20.8% paper, 17.9% plastic, 0.2% others. The Waste Processing Site (TPS) is designed to suit the needs of SMAN 1 Kapuas Barat. Keywords: Waste Generation, Waste Composition, SMAN 1 Kapuas Barat, Waste Treatment Site (TPS)